A study on factors influencing Malaysian university students’ intention to utilise ChatGPT - Lim, Joanne; Lee, Vanessa Xin Ci; Thivashini, Iyakannu (2024)
The aim of this research is to explore the relationship between factors influencing ChatGPT adoption and the Technology Acceptance Model (TAM) involving key variables such as perceived ease of use, perceived usefulness, and attitude, toward the behavior intention to utilize ChatGPT among university students in Malaysia. This study was conducted around 384 university students from two types of institutions which involved public institutions and private higher education institutions in Malaysia. IBM Statistical Package for the Social Sciences tool (SPSS) was used to analyze and interpret the relevant data. The data was analyzed by using descriptive analysis, reliability test, Pearson Correlation Coefficient, and Multiple Linear Regression. The findings revealed that perceived usefulness and attitude towards using had significant positive effects on student's intention to adopt ChatGPT, while perceived ease of use played a not significant role. However, limitations and recommendations for future research are further discussed in this study as well. Keywords: Artificial intelligence (AI), ChatGPT, Technology Acceptance Model (TAM), Perceived Ease of Use, Perceived Usefulness, Attitude, Behavior Intention